SHELF LIFE EVALUATION OF BUFFALO SAUSAGES SUPPLEMENTED WITH DIFFERENT FAT SOURCES AND STORAGE CONDITIONS - K. Nauman1; M. T. Akbar; M. H. Jaspal; S. Ali; J. Nasir; B. Asghar; S. Mehmood (Journal of Animal and Plant Sciences, 2020)
The study was undertaken to evaluate supplementation of different fat sources (buffalo kidney, pelvic, heart (KPH) fat, sheep tail fat, palm kernel butterfat) on shelf life parameters (thiobarbituric acid values (TBARs), total viable count (TVC), water activity (aw) and color values) in sausages of buffalo calves at different storage temperature and storage duration. Sausages were prepared by employing the hurdle technology that includes mixing of minced buffalo meat and 20% fat with spice mixture, ascorbic acid, 0.5% Nitrite-NaCl, phosphate, 5% potassium ascorbate spray. Sausages were stored at refrigerated (2±2 °C) and in an incubator to mimic high ambient temperature (35±2 °C) until 11 days or acceptable limits. The data were analyzed through factorial ANOVA. Results show that hurdle treatment collectively increased the shelf life by significantly reducing quality deterioration during storage. Lowest color lightness (L*) values were recorded in animal-based fat sausages, while the redness (a*) values were increased during the storage, and maximum values were observed during storage at ambient temperature. Sheep tail fat sausages exhibited the highest TBARs and TVC values. Similarly, storage temperature and duration affected the quality characteristics, samples stored at an ambient temperature markedly increased the TBARS, TVC and color throughout the storage duration, whereas Aw value decreased. Palm kernel butterfat (PKBF) sausages show higher lightness (L*) and yellowness (b*) values and lower redness(a*) values than buffalo kidney, pelvic, heart (KPH) fat and sheep tail fat (STF) sausages. PKBF sausages showed lowest TVC values represented in terms of log cfu/g while the highest values were observed in STF sausages; however, KPH sausages showed mediate values. Based on these results, it was concluded that sausages made from palm kernel butter fat showed the highest shelf life as compared to the animal source fat sources.
Keywords: kidney pelvic heart fat; sheep tail fat; palm kernel butterfat; beef sausages; shelf stability